Notoginsenoside Fc ameliorates renal tubular injury and mitochondrial damage in acetaminophen-induced acute kidney injury partly by regulating SIRT3/SOD2 pathway - Wei, Miaomiao; Gao, Yuancheng; Cheng, Dongsheng; Zhang, Haiying; Zhang, Wei; Shen, Yilan; Huang, Qunwei; An, Xiaoning; Wang, Bing; Yu, Zhonghai; Wang, Niansong; Chen, Hongbo; et al. (Frontiers in Medicine, 2023)
Mitochondria dysfunction is one of the primary causes of tubular injury in acute kidney injury (AKI). Notoginsenoside Fc (Fc), a new saponin isolated from Panax notoginseng, exhibited numerous pharmacological actions. However, the beneficial effects of Fc on renal tubular impairment and mitochondrial dysfunction in AKI have not been fully studied. In this study, we established acetaminophen (APAP)-induced AKI model in mice to examine the therapeutic impacts of Fc on AKI. Our results showed that Fc could decrease the levels of the serum creatinine (Scr), blood urea nitrogen (BUN) and Cystatin C in mice with AKI. Fc also ameliorated renal histopathology, renal tubular cells apoptosis and restored expression of apoptosis-related proteins such as Bax, Bcl-2, and caspase3 (C-caspase3). Additionally, Fc increased the protein expression of SIRT3 and SOD2 in kidneys from mice with AKI. In vitro studies further showed Fc reduced the apoptosis of HK-2 cells exposure to APAP, attenuated the loss of mitochondrial membrane potential and decreased the formation of mitochondrial superoxide. Fc also partly restored the protein expression of Bax, Bcl-2, C-Caspase3, SIRT3 and SOD2 in HK-2 cells exposure to APAP. In summary, Fc might reduce renal tubular injury and mitochondrial dysfunction in AKI partly through the regulation of SIRT3/SOD2 pathway.